In-house development of an FPGA-based MCA8K for gamma-ray spectrometer - Lanh, Dang (Springerplus, 2014)
The objective of this work is domestic development of electronics instruments. It used for measuring ionization radiation and practical training at Nuclear Research Institute (NRI), Dalat, Vietnam. The aim of this work is to study and develop a novel MCA8k for Gamma-ray spectrometer concerning experimental nuclear physics. An approach for design and construction of the aforementioned instrument is to apply logic integrating techniques via Field Programmable Gate Arrays (FPGA) under Max + PlusII, Altera. The instrument allows interfacing to PC with self-developed application software. Scientific significance of this work is partly to contribute to opening a research direction in the field of nuclear electronics science for design and construction of radiation measurement instruments with the advanced IC technology in Vietnam. Practical significance of this work is partly to contribute to enhancement of capabilities in developing radiation measurement instruments for experimental research as well as practical training in nuclear physics. The advantages of FPGA: overcoming ballistic deficit, decrement of serial and parallel noise, flexible in programming, control of the system by software without an interfere of hardware. The disadvantages of FPGA: requirement of good knowledge of VHDL and professional tools for development of a expected project. A new electronics module of MCA8k has been achieved. Some main results obtained from the experimental testing are as follows: differential nonlinearity (DNL) of FPGA-MCA8k approximately 1.27%, integral nonlinearity (INL) = 0.607%, time conversion ≈ 2.2 μs, deadtime (DT) is 0.75%. Data Acquisition Program MCANRI written in VC (+ +)6.0, self-executed under Windows XP environment.